Neighborhood built environment and cognition in non-demented older adults: The Multi-Ethnic Study of Atherosclerosis. (March 2018) - Besser, Lilah M.; Rodriguez, Daniel A.; McDonald, Noreen; Kukull, Walter A.; Fitzpatrick, Annette L.; Rapp, Stephen R.; Seeman, Teresa
Abstract: Preliminary studies suggest that neighborhood social and built environment (BE) characteristics may affect cognition in older adults. Older adults are particularly vulnerable to the neighborhood environment due to a decreasing range of routine travel with increasing age. We examined if multiple neighborhood BE characteristics are cross-sectionally associated with cognition in a diverse sample of older adults, and if the BE-cognition associations vary by individual-level demographics. The sample included 4539 participants from the Multi-Ethnic Study of Atherosclerosis. Multivariable linear regression was used to examine the associations between five BE measures and four cognitive measures, and effect modification by individual-level education and race/ethnicity. In the overall sample, increasing social destination density, walking destination density, and intersection density were associated with worse overall cognition, whereas increasing proportion of land dedicated to retail was associated with better processing speed. Effect modification results suggest that the association between urban density and worse cognition may be limited to or strongest in those of non-white race/ethnicity. Although an increase in neighborhood retail destinations was associated with better cognition in the overall sample, these results suggest that certain BE characteristics in dense urban environments may have a disproportionately negative association with cognition in vulnerable populations. However, our findings must be replicated in longitudinal studies and other regional samples. Highlights: The neighborhood built environment may affect cognition and brain aging. Few have studied built environment and cognition associations in older age. Three measures consistent with urban density were associated with worse cognition. Increased neighborhood retail destinations was associated with better cognition. Negative associations were mostly limited to those of non-white race/ethnicity.